2003
DOI: 10.1124/jpet.103.049825
|View full text |Cite
|
Sign up to set email alerts
|

The Reinforcing Efficacy of Psychostimulants in Rhesus Monkeys: The Role of Pharmacokinetics and Pharmacodynamics

Abstract: This study was undertaken to investigate pharmacological variables that influence the reinforcing efficacy of psychostimulants. Rhesus monkeys (n ϭ 9) responded under a withinsession, exponentially increasing, progressive ratio schedule of cocaine reinforcement. Doses of cocaine, methylphenidate (MP), cocaine analogs [(Ϯ)-2␤-propanoyl-3␤-(2-naphthyl)-tropane (WF-23), HD-23; (Ϯ)-2␤-propanoyl-3␤-(2-isopropenyl)-tropane (WF-60), HD-60; and 2␤-propanoyl-3␤-(4-tolyl)-tropane (HD-11, WF-11), and 2␤-propanoyl-3␤-(4-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
64
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 29 publications
6
64
2
Order By: Relevance
“…Similarly, a piperidine cocaine analog, which has slightly weaker affinity at the DAT than cocaine, was a weaker reinforcer than cocaine . However, when a correlation between efficacy as a reinforcer and potency at the DAT was made among seven monoamine transporter inhibitors, no relationship was found (Lile et al, 2003). Interestingly, the present study found a negative relationship between binding affinities at the DAT in vivo and reinforcing efficacy and between binding affinities at the DAT in vitro and reinforcing efficacy.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Similarly, a piperidine cocaine analog, which has slightly weaker affinity at the DAT than cocaine, was a weaker reinforcer than cocaine . However, when a correlation between efficacy as a reinforcer and potency at the DAT was made among seven monoamine transporter inhibitors, no relationship was found (Lile et al, 2003). Interestingly, the present study found a negative relationship between binding affinities at the DAT in vivo and reinforcing efficacy and between binding affinities at the DAT in vitro and reinforcing efficacy.…”
Section: Discussioncontrasting
confidence: 85%
“…In two-drug comparisons, diminished reinforcing efficacy of a piperidine analog or a tropane analog (Lile et al, 2002) relative to cocaine was attributed to its slower rate of onset. On the other hand, in a comparison across several drugs, no obvious relationship between rate of onset and reinforcing efficacy was observed (Lile et al, 2003). Therefore, the relationship between onset of action and reinforcing efficacy across DAT ligands remains equivocal.…”
Section: Introductionmentioning
confidence: 94%
“…Although the present results lend support, the conclusion that increased 5-HT actions relative to DA can decrease reinforcing strength, it should be pointed out that Lile et al (2003) reported self-administration by monkeys of a cocaine analog and DA uptake blocker, HD-60, with at least 80-fold selectivity for SERT relative to the DAT binding. Other compounds tested in monkeys that support the DA/5-HT hypothesis have been primarily monoamine releasers (Ritz and Kuhar 1989;Wee et al 2005), raising the possibility that there is a difference between monoamine release and reuptake blockade in terms of reinforcing effects.…”
Section: Discussioncontrasting
confidence: 52%
“…When cocaine was infused more slowly, it was found to be less effective as a reinforcer in nonhuman primates (Balster and Schuster, 1973;Panlilio et al, 1998). Similarly, the cocaine analog HD-23, which takes 60 min to attain significant binding was not as reinforcing in rhesus monkeys as were cocaine or methylphenidate (Lile et al, 2003). The piperazine analog (+)-CPCA binds to DAT more slowly than cocaine and was found to be a less robust reinforcer than cocaine in nonhuman primates (Woolverton et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…A recent review suggests that a rapid onset of action is associated with the reinforcing effects of a drug but is not required for a drug to act as a reinforcer (Lile, 2006). Similarly, several other phenylpiperazine and phenyltropane DAT inhibitors function as positive reinforcers in nonhuman primates despite a slow onset of DAT binding Lile et al, 2003;Spealman and Kelleher, 1981). Indeed, decreasing the rate of cocaine infusion in rhesus monkeys decreased the reinforcing strength of the drug, but only to a certain point, suggesting a "floor" effect in the absence of alternate reinforcers (Woolverton and Wang, 2004).…”
Section: Discussionmentioning
confidence: 99%